POEM Is a Durable Treatment in Children and Adolescents With Achalasia Cardia - Nabi, Zaheer; Ramchandani, Mohan; Basha, Jahangeer; Goud, Rajesh; Darisetty, Santosh; Reddy, Duvvur Nageshwar (Frontiers in Pediatrics, 2022)
Background and Aim Per-oral endoscopic myotomy (POEM) is emerging as an effective treatment for pediatric achalasia. There are limited data on the long-term efficacy of POEM in children and adolescents with achalasia. In this study, we aim to evaluate the outcomes of POEM at ≥4 years follow-up. Method The data of consecutive children who underwent POEM (September 2013–July 2021) and completed at least 4 years follow-up were analyzed retrospectively. The primary outcome was clinical success (Eckardt ≤ 3) at ≥4 years follow-up. The secondary outcomes included the prevalence of gastroesophageal reflux disease (GERD) and predictors of recurrent symptoms (Eckardt ≥2) after POEM. Results A total of 69 children underwent POEM for achalasia during the study period. Of these, 41 (59.4%) children completed ≥4 years [mean 68.5 months (range 48–94)] follow-up, and 38 were included in the final analysis. The subtypes of achalasia included type I (28.9%), type II (60.5%), and type III (2.6%). There was a history of prior treatment in 11 children (28.9%). Clinical success was recorded in 36 (94.7%) patients who successfully underwent POEM. Recurrent symptoms (Eckardt ≥ 2) were noticed in 12 (31.6%) children at ≥4 years. On multivariate analysis, there were no identifiable factors which predicted recurrent symptoms after POEM. Symptomatic GERD and erosive esophagitis were detected in 13.8% (4/29) and 57.1% (8/14) of the children, respectively. Conclusion POEM is a durable treatment modality for achalasia in the pediatric population irrespective of the sub-type of achalasia and history of prior treatment.